Analysis of Issues in the Use of Fraudulent Power of Attorney in the Preparation of Sale and Purchase Deeds - Melisa, Mia (Green Publisher Indonesia, 2025)
The Power of Attorney to Sell can be used as the basis for drafting a Sale and Purchase Deed if the seller cannot be present during the signing. However, in practice, the Power of Attorney to Sell is often misused for purposes that violate the law, such as the illegal appropriation of land by individuals or groups aiming to seize ownership of others' land unlawfully, as well as the use of falsified Powers of Attorney to Sell as the basis for drafting Sale and Purchase Deeds before the Land Deed Official. This study examines and analyzes the legal consequences and the application of the principle of prudence by Notaries and Land Deed Officials in relation to the forgery of the Power of Attorney to Sell in the drafting of Sale and Purchase Deeds. It also evaluates the legal standing of falsified Powers of Attorney to Sell as the basis for creating Sale and Purchase Deeds, which can result in criminal, civil, and administrative sanctions. This study's findings demonstrate that applying the principle of prudence by Notaries and Land Deed Officials is crucial to preventing misuse and maintaining public trust in authentic deeds.